2023
DOI: 10.1017/s2045796023000549
|View full text |Cite
|
Sign up to set email alerts
|

Substance use before or during pregnancy and the risk of child mortality, perinatal morbidities and congenital anomalies

Abstract: Aims We aimed to investigate child mortality, perinatal morbidities and congenital anomalies born by women with substance misuse during or before pregnancy (DP or BP). Methods Taiwan Birth Registration from 2004 to 2014 linking Integrated Illicit Drug Databases used to include substance misuse participates. Children born by mothers convicted of substance misuse DP or BP were the substance-exposed cohort. Two substance-unexposed comparison cohorts were established: one comparison cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Most illicit substances would affect embryos through the placenta and may cause obstetric complications, excess mortality, neonatal abstinence syndrome, abnormal physical problems, or neurodevelopment issues (7,8). Prior research and our previous study have shown elevated risks of short-term neonatal outcomes, such as the abstinence syndrome, stillbirths, low birth weight (9), congenital heart defects, small head circumferences, or neural tube defects in children born by mothers exposed to opioid, heroin, or amphetamine during pregnancy (10)(11)(12). Few studies have mentioned the raised long-term risks of prenatal exposures of opioids or heroin on children's intellectual functions or neurobehavioral disorders, such as autistic disorder or attention de cit hyperactivity disorder (ADHD) after birth (13,14).…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Most illicit substances would affect embryos through the placenta and may cause obstetric complications, excess mortality, neonatal abstinence syndrome, abnormal physical problems, or neurodevelopment issues (7,8). Prior research and our previous study have shown elevated risks of short-term neonatal outcomes, such as the abstinence syndrome, stillbirths, low birth weight (9), congenital heart defects, small head circumferences, or neural tube defects in children born by mothers exposed to opioid, heroin, or amphetamine during pregnancy (10)(11)(12). Few studies have mentioned the raised long-term risks of prenatal exposures of opioids or heroin on children's intellectual functions or neurobehavioral disorders, such as autistic disorder or attention de cit hyperactivity disorder (ADHD) after birth (13,14).…”
Section: Introductionmentioning
confidence: 65%
“…Children born to mothers with illicit drug use before or during pregnancy were our study cohort. (9), We established the study cohort by identifying pregnant women being arrested by the police due to illicit substance use from the 'Substance Abuse Control Databases'.…”
Section: Study Subjectsmentioning
confidence: 99%
See 3 more Smart Citations